Anaemia among men in India: a nationally representative cross-sectional study - Didzun, Oliver; De Neve, Jan-Walter; Theilmann, Michaela; Bärnighausen, Till (The lancet. Global health, 2019)
Background - Population-based studies on anaemia in India have mostly focused on women and children, with men with anaemia receiving much less attention despite anaemia's adverse effect on health, wellbeing, and economic productivity. This study aimed to determine the national prevalence of anaemia among men in India; how the prevalence of anaemia in men varies across India among states and districts and by sociodemographic characteristics; and whether the geographical and sociodemographic variation in the prevalence of anaemia among men is similar to that among women to inform whether anaemia reduction efforts for men should be coupled with existing efforts for women. - Methods - In this cross-sectional study, we analysed data from a nationally representative household survey carried out from January, 2015, to December, 2016, among men aged 15-54 years and women aged 15-49 years in all 29 states and seven Union Territories of India. Haemoglobin concentration was measured using the portable HemoCue Hb 201+ (HemoCue AB, Ängelholm, Sweden) and a capillary blood sample. In addition to disaggregating anaemia prevalence (separately in men and women) by state and age group, we used mixed-effects Poisson regression to determine individual-level and district-level predictors of anaemia. - Findings - 106 298 men and 633 305 women were included in our analysis. In men, the prevalence of any anaemia was 23·2% (95% CI 22·7-23·7), moderate or severe anaemia was 5·1% (4·9-5·4), and severe anaemia was 0·5% (0·5-0·6). An estimated 21·7% (20·9-22·5) of men with any degree of anaemia had moderate or severe anaemia compared with 53·2% (52·9-53·5) of women with any anaemia. Men aged 20-34 years had the lowest probability of having anaemia whereas anaemia prevalence among women was similar across age groups. State-level prevalence of any anaemia in men varied from 9·2% (7·7-10·9) in Manipur to 32·9% (31·0-34·7) in Bihar. The individual-level predictors of less household wealth, lower education, living in a rural area, smoking, consuming smokeless tobacco, and being underweight and the district-level predictors of living in a district with a lower rate of primary school completion, level of urbanisation, and household wealth were all associated with a higher probability of anaemia in men. Although some important exceptions were noted, district-level and state-level prevalence of anaemia among men correlated strongly with that among women. - Interpretation - Anaemia among men in India is an important public health problem. Because of the similarities in the patterns of geographical and sociodemographic variation of anaemia between men and women, future efforts to reduce anaemia among men could target similar population groups as those targeted in existing efforts to reduce anaemia among women. - Funding - Alexander von Humboldt Foundation.
Gesehen am 24.04.2020